Reference Income Effects in the Determination of Equivalence Scales Using Income Satisfaction Data - Melanie Borah; Andreas Knabe; Carina Kuhställer (Center for Economic Studies and ifo Institute (CESifo), 2016)
We estimate household equivalence scales using income satisfaction data from the German Socio-Economic Panel. We extend previous studies applying this approach by taking reference income into account. This allows separating needs-based from reference effects in the determination of income satisfaction. We show that this adjustment helps to overcome a bias causing an overestimation of adults' and an underestimation of children's needs-based equivalence weights. Our results indicate that controlling for income comparisons eliminates the gap between equivalence scale parameters for adults and children found in other studies.
Keywords: I32; J13; D31; 330; equivalence scale; income satisfaction; relative income